2002
DOI: 10.2136/sssaj2002.8570
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Soil Fertility Trends in a 20‐Year Rice–Rice–Wheat Experiment in Nepal

Abstract: Declining yields and soil nutrient balance in a long-term rice-rice-wheat study suggest depletion of soil potassium (K) and inadequate K fertilization seem to be primary reasons for limited and declining crop yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 27 publications
6
69
0
Order By: Relevance
“…Compared with the control, all fertilization treatments had no significant effects on soil pH and SOC contents (P > 0.05), but generally increased nutrients content when corresponding elements were applied (Table 2). These findings are in agreement with the results of Regmi et al (2002) and Zhang et al (2009), who reported that the contents of N, P and K were increased when compared with those of no fertilizer control. Furthermore, soil bulk densities (SBD) in NPK and 2NPK treatment were significantly lower than those in control and N (P < 0.05).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the control, all fertilization treatments had no significant effects on soil pH and SOC contents (P > 0.05), but generally increased nutrients content when corresponding elements were applied (Table 2). These findings are in agreement with the results of Regmi et al (2002) and Zhang et al (2009), who reported that the contents of N, P and K were increased when compared with those of no fertilizer control. Furthermore, soil bulk densities (SBD) in NPK and 2NPK treatment were significantly lower than those in control and N (P < 0.05).…”
Section: Resultssupporting
confidence: 93%
“…Generally, rice yield in the longterm experiments remained stable when recommended doses of N, P and K were applied , Ladha et al 2003). Where yield declines occurred, the major causes were attributable to inappropriate fertilizer managements , Ladha et al 2003, prolonged soil wetness , delay in sowing (Regmi et al 2002), and increased nighttime temperature associated with global warming (Peng et al 2004).…”
mentioning
confidence: 99%
“…Hobbs and Morris (1996) observed a 1% decrease for each day that wheat sowing was postponed after the optimum sowing date (15)(16)(17)(18)(19)(20) November). Regmi et al (2002) also reported a yield decline in wheat when it was sown after the third week of November. A major reason for late sowing is the late harvest of the preceding crops.…”
mentioning
confidence: 97%
“…Several other scientists (Zia et al, 2007;Singh and Tripathi, 2008;Reddy et al, 2010) reported the results in conformity with the results of present study. Regmi et al, (2003) also found consistently higher yield of rice in the NPK treatments than in treatments where one or more nutrients were lacking in case of a 20-years experiment. Further, 100% NPK + 5 Kg/ha Zn (along with S @ 40 kg/ha) in case of rice was reported to be best for the farmers so far as grain yield, straw yield and nutrient uptake values are concerned (Trivedi et al, 2015).…”
Section: Resultsmentioning
confidence: 57%